PENDIDIKAN KARAKTER PADA TRADISI PAMALI - Andi Asdar; Mujahidah (PT. CASA CENDEKIA MEDIA, 2025)
The pamali tradition is part of the local wisdom of the Bugis community, containing various customary prohibitions passed down from generation to generation. This tradition is believed not only to function as a set of restrictions but also as a medium for moral and ethical development within social life. This study aims to identify the forms of pamali traditions that are still practiced by the community, the character education values embedded within them, and the application of pamali values in the lives of Bugis people in Maros Regency. This research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The research instruments include interview guidelines, observation sheets, and documentation records. Data analysis was conducted through data reduction, data display, and conclusion drawing. The validity of the data was tested using triangulation of techniques, sources, and time. The findings reveal that the Bugis pamali tradition embodies character values such as religiosity, responsibility, discipline, honesty, politeness, and social awareness. The tradition continues to be practiced and transmitted through the roles of traditional leaders, religious figures, parents, and the wider community as a form of cultural preservation as well as character education for younger generations. The values embedded in the pamali tradition align with the principles of national character education and Islamic value perspectives in shaping the morals and personality of the nation’s youth.